2020
DOI: 10.1101/2020.08.02.232710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Permutation tests for hypothesis testing with animal social network data: problems and potential solutions

Abstract: Generating insights about a null hypothesis requires not only a good dataset, but also statistical tests that are reliable and actually address the null hypothesis of interest. Recent studies have found that permutation tests, which are widely used to test hypotheses when working with animal social network data, can suffer from high rates of type I error (false positives) and type II error (false negatives). Here, we first outline why pre-network and node permutation tests have elevated type I and II error rat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…This included recalculating the network parameters after randomly swapping the nodes of the original networks. We used node-swapping (as opposed to generating random graphs or using pre-network 'edgeswapping' randomizations) since this approach seemed better suited for our purposes of testing regression-based null hypotheses in a taxon with a largely stable group composition and relatively low observation biases 44,45 . Speci cally, node-swapping preserves the overall size, number of connections, and structure of the network, thereby also preserving the overall distribution of node-level measures such as degree and EC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This included recalculating the network parameters after randomly swapping the nodes of the original networks. We used node-swapping (as opposed to generating random graphs or using pre-network 'edgeswapping' randomizations) since this approach seemed better suited for our purposes of testing regression-based null hypotheses in a taxon with a largely stable group composition and relatively low observation biases 44,45 . Speci cally, node-swapping preserves the overall size, number of connections, and structure of the network, thereby also preserving the overall distribution of node-level measures such as degree and EC.…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, node-swapping preserves the overall size, number of connections, and structure of the network, thereby also preserving the overall distribution of node-level measures such as degree and EC. It is therefore a more conservative approach that may be less susceptible to Type I errors, compared to random graph generation or edge-swapping 44,45 . After each permuted swapping event, we re t the same GLMM using these newly created parameters as response variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies found that (datastream and node) permutation tests, which are widely used to test hypotheses in animal social network analyses, can produce high rates of type I error (false positives) and type II error (false negatives) (Franks et al 2020; Puga□Gonzalez et al 2020; Weiss et al 2020; Farine and Carter 2020). In order to ensure that the results provided by our GAI analyses are reliable and account for both social and non-social nuisance effects, we used an approach proposed by Farine and Carter (2020) that uses datastream permutations to control for nuisance effects, then uses node permutations to test for the statistical significance of the effect of interest. It first uses datastream permutations to calculate the deviation of each of a node-level or edge-level metric from its random expectation given the structure of the observation data (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This approach is similar to generalised affiliation indices (Whitehead and James 2015), but it uses datastream permutation tests, rather than regression models, to estimate the deviance from random. This approach demonstrated its robustness to test the role of kinship in shaping the strength of interactions between individuals in the presence of other social effects such as the presence of non-kin social bonds (Farine and Carter 2020). We therefore applied this double-permutation procedure to test for the role of kinship in driving associations among sharks as well as the role of sex on node centrality (controlling for the number of observations) and to confirm the robustness of our previous results to high type I and type II error rates.…”
Section: Methodsmentioning
confidence: 99%